2022
DOI: 10.7573/dic.2021-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and usability of the recombinant chorionic gonadotropin prefilled pen: a survey in Italy

Abstract: Background Due to high purity, recombinant human chorionic gonadotropin (hCG) is suitable for subcutaneous injection, and hence for self-administration, in assisted reproduction. To increase usability and reduce the risk of dosing errors, a prefilled pen was produced. We investigated the ease of administration and satisfaction with the product amongst patients and healthcare professionals. Methods A survey was conducted amongst women with infertility who underwent in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
0
10
2
Order By: Relevance
“… 21 A second study conducted among patients undergoing ART also reported that avoiding dosage mistakes was of great importance. 13 Ease of use was identified in previous studies as the most important attribute by patients undergoing ART, however, in the current study this attribute was perceived as of below average importance. 13 , 21 Similar differences between patient and nurse perceptions were found in a previous study, which examined FSH injection pen perception in the European market.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“… 21 A second study conducted among patients undergoing ART also reported that avoiding dosage mistakes was of great importance. 13 Ease of use was identified in previous studies as the most important attribute by patients undergoing ART, however, in the current study this attribute was perceived as of below average importance. 13 , 21 Similar differences between patient and nurse perceptions were found in a previous study, which examined FSH injection pen perception in the European market.…”
Section: Discussioncontrasting
confidence: 58%
“… 13 Ease of use was identified in previous studies as the most important attribute by patients undergoing ART, however, in the current study this attribute was perceived as of below average importance. 13 , 21 Similar differences between patient and nurse perceptions were found in a previous study, which examined FSH injection pen perception in the European market. 21 This implies a possible trend in perception differences between nurses and patients, where each group tends to place a greater value on attributes that affect their daily lives.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations